Brazilian social media disseminates (mis) information on diabetes and periodontal disease (Research, Society and Development, 2022)
Objective: To analyze Brazilian YouTube videos on diabetes mellitus (DM) and periodontal diseases (PD) to assess the usefulness of the content. Methodology: Observational, cross-sectional, and semiquantitative study carried out on YouTube on 01/04/2018, using the term 'diabetes and periodontal disease'. The 200 videos associated with the search term were considered, and those not recorded in Portuguese were excluded; unrelated topic; duplicates; and with more than 50 minutes. Videos were categorized as very helpful, moderately helpful, not very helpful, and not helpful in informing the public. Results: Of the 200 videos in the study, 123 met the inclusion criteria, were analyzed, and resulted in: 1,227,134 views, 13,269 likes, 659 dislikes, 927 comments, and over 26 hours of total duration. Lay people were the primary source of uploading videos on YouTube (n=56; 45.52%), and health professionals the primary authorship. There was no statistical difference (p< 0.05) when analyzing the level of usefulness of the videos' content, as well as the likes and dislikes reactions, comments, duration, and views of the videos between different levels of usefulness. Only 7.14% of the videos were categorized as very useful, 37.50% as moderately useful, 50.00% as not very useful, and 5.36% as not useful to inform about DM and PD. Non-useful videos were the most popular. Conclusions: This study's Brazilian YouTube videos on DM and PD are popular and have varied sources and content. Most of the content is not useful. Therefore, such videos cannot be considered useful as a source of information on the topic.